(untitled) (Journal of Education and Development, 2020)
Students of color and low-income students are at a much higher risk of dropping out of school than more privileged students. Dropping out of school can lead to severe social issues – students who drop out of school are much more likely to end up incarcerated and to remain unemployed for long periods of time. However, strong empirical research indicates that certain teaching methods are highly beneficial for the academic achievement of at-risk students in addition to being beneficial for the achievement of all students in general. These teaching methods are based around direct, teacher-centered instruction. In contrast, teaching methods based around minimally-guided instruction tend to be ineffective (or even detrimental) for at-risk students. This text outlines the benefits of direct instruction and the potential risks of minimally-guided instruction, along with specific steps for implementing effective teaching strategies.